DNA Sequences Encoding CD4(+) and CD8(+) T-Cell Epitopes Are Important for Efficient Protective Immunity Induced by DNA Vaccination with a Trypanosoma cruzi Gene - Fujimura, Adriana E. (American Society for Microbiology, 2001)
Immunization of BALB/c mice with a plasmid containing the gene for Trypanosoma cruzi trans-sialidase (TS) induced antibodies that inhibited TS enzymatic activity, CD4(+) Th1 and CD8(+) Tc1 cells, and protective immunity against infection. We used this model to obtain basic information on the requirement of CD4 or CD8 or B-cell epitopes for an effective DNA-induced immunity against T. cruzi infection. For that purpose, mice were immunized with plasmids containing DNA sequences encoding (i) the entire TS protein, (ii) the TS enzymatic domain, (iii) the TS CD4(+) T-cell epitopes, (iv) the TS CD8(+) T-cell epitope, or (v) TS CD4(+) and CD8(+) T-cell epitopes. Plasmids expressing the entire TS or its enzymatic domain elicited similar levels of TS-inhibitory antibodies, γ interferon (IFN-γ)-producing T cells, and protective immunity against infection. Although the plasmid expressing TS CD4 epitopes was immunogenic, its protective efficacy against experimental infection was limited. The plasmid expressing the CD8 epitope was poorly immunogenic and provided little protective immunity. The reason for the limited priming of CD8(+) T cells was due to a requirement for CD4(+) T cells. To circumvent this problem, a plasmid expressing both CD4(+) and CD8(+) T-cell epitopes was produced. This plasmid generated levels of IFN-γ-producing T cells and protective immunity comparable to that of the plasmid expressing the entire catalytic domain of TS. Our observations suggest that plasmids expressing epitopes recognized by CD4(+) and CD8(+) T cells may have a better protective potential against infection with T. cruzi.